2001
DOI: 10.1007/bf02410103
|View full text |Cite
|
Sign up to set email alerts
|

The role of stem inoculum in the transmission ofFusarium sulphureum to potato tubers

Abstract: SummaryOver 2 years, seed tubers or stems were inoculated with Fusarium sulphureum Schlecht. (F. sambucinum Fuckel f. 6 Wollenw.) and the incidence of dry rot on daughter tubers assessed by standardised wound tests. The amount of stem and soil inoculum was also measured in one year.Inoculating stem bases resulted in greater concentrations of spores on the stem bases, greater soil populations at harvest and more dry rot on tubers than inoculating the seed tuber. Overall, the incidence of dry rot and the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The pathogen may also get introduced to new locations through contaminated soil which adheres to the farm implements, through wind and irrigation water etc. Studies have demonstrated that transmission of F. sulphureum to progeny tubers was greater from highly contaminated seed than from rotting seed whereas in case of F. coeruleum , the disease transmitted readily from the rotted mother tuber Choiseul et al 2001 ). This was attributed to the different capacity of each species of the pathogen to sporulate underground on seed tubers and on stem bases.…”
Section: Epidemiologymentioning
confidence: 96%
See 2 more Smart Citations
“…The pathogen may also get introduced to new locations through contaminated soil which adheres to the farm implements, through wind and irrigation water etc. Studies have demonstrated that transmission of F. sulphureum to progeny tubers was greater from highly contaminated seed than from rotting seed whereas in case of F. coeruleum , the disease transmitted readily from the rotted mother tuber Choiseul et al 2001 ). This was attributed to the different capacity of each species of the pathogen to sporulate underground on seed tubers and on stem bases.…”
Section: Epidemiologymentioning
confidence: 96%
“…This was attributed to the different capacity of each species of the pathogen to sporulate underground on seed tubers and on stem bases. F. coeruleum sporulates profusely on the surface of rotting seed tubers, whereas F. sulphureum sporulates more readily on stem bases (Adams and Lapwood 1983 ;Choiseul et al 2001 ).…”
Section: Epidemiologymentioning
confidence: 98%
See 1 more Smart Citation
“…It was observed that F. sulphureum transmission is greater from contaminated seed tuber while F. coeruleum transmits more readily from rotten mother tuber. F. sulphureum preferably sporulates on stem bases whereas F. coeruleum rapidly sporulates outside rotten tubers (Choiseul et al 2001;Cullen et al 2005;Bojanowski et al 2013). The optimum temperature for mycelial growth of F. sambucinum, F. graminearum, F. oxysporum, F. solani and F. culmorum is 20-25 °C whereas for sporulation 25-30 °C temperature is required.…”
Section: Infection-related To Dry Rot and The Life Cycle Of The Fusarium Speciesmentioning
confidence: 99%